The effect of internal market orientation on employee job satisfaction: a study of Malaysian childcare centre - Othman, Abdul Rahim; Perumal, Selvan; Hashim, Noor Azmi (American Research Institute for Policy Development, 2014)
The number of childcare centres in Malaysia has been steadily increasing and is expected to continue to increase in the future.This is largely due to the active campaign of the Malaysian Government for early childhood education, which is based on the important role played by formal early childhood education. This paper examines the effect of the internal market orientation and employee job satisfaction.To examine the model of the study, 692 questionnaires were distributed.Out of that 360 responses were received from a population comprising the Malaysian childcare center.Employing SPSS approach, the hypotheses of the study were tested.The findings imply the need for childcare centres.This could enhance its sustainability, competitiveness and innovation following market trends.